This Essay Has a Soundtrack - Arnold, Martin (Imaginations: Journal of Cross-Cultural Image Studies, 2025)
"This Essay Has a Soundtrack" really does have a soundtrack. It is a piece of music composed, performed and recorded by the author that uses a processed version of the essay as its score. The recording of the composition is offered as a possible musical accompaniment to reading the score. While this places such a reading within the field of research-creation, the essay actually engages this field more through speculating about the essay form as a fluid, open, indeterminate and unsubstantiated thing that can, as Adorno puts it: "blow open what cannot be absorbed by concepts.” This engagement with the poetic, aesthetic potentials of the essay serves as an entrance to touching on aesthetic theory more generally, in contact with Montaigne, Adorno, Born, Menke, Seel, Lyotard, Culler, Cazdyn, and Trinh Minh-ha among others. While the essay suggests readers should search for and experiment with alternatives to the translation and interpretation of metaphors when thinking research-creation, the author, does this more as a performance, banging around in-between the thought of others, rather than as a sustained, cogent argument.